Coral-dwelling Caribbean gobies exhibit distinct skin microbiota compared to other sympatric species - Ana Pereira; Raquel Xavier; Anya Brown; Jeanne Bloomberg; Gina C. Hendrick; Matthew D. Nicholson; Mallory Kastner; Marta C. Soares; Amy Apprill; Paul C. Sikkel (Coral Reefs, 2026)
Microbial communities fundamentally shape ecosystem function and biodiversity across all biological systems through complex dynamics. In coral reef ecosystems, understanding the dynamics of these microbial communities has become critical for predicting reef responses to environmental stressors. Fish skin microbiota are highly susceptible to environmental changes and may vary significantly across species and geographic locations, yet the extent to which these variations occur remain poorly understood. Here, we compared the skin microbiota of four closely related and sympatric cryptobenthic gobiid species, that exhibit different behavioral ecologies (cleaning vs.non-cleaning), ecological niches (water column, coral-, or sand-dwelling) and phylogenetic affinities ( Elacatinus vs. Coryphopterus ), yet reside in the same reef patches in St. Croix and Puerto Rico, eastern Caribbean. Coral-dwelling gobies, including cleaning sharknose and non-cleaning peppermint gobies, exhibited significantly lower microbial diversity compared to reef-hovering and sand-dwelling species (both non-cleaning). These coral dwellers showed unique microbial signatures despite having similar alpha diversity levels. Core microbiota analysis also revealed striking differences between coral-dwelling and reef-hovering/sand-dwelling species, with the core microbiome of the former dominated by Vibrio , Pseudoalteromonas , and Alteromonas in the case of cleaning gobies and by Endozoicomonas in the case of peppermint gobies, while reef-hovering and sand-dwelling gobies exhibited diverse core microbiota with greater overlap between species. Ecological niche occupancy and reef habitat selection appear to be primary drivers of skin microbiota composition in gobiid fishes, rather than cleaning behavior and/or host phylogenetic affinities alone, though species-specific skin mucus properties likely also contribute to selective bacterial colonization patterns.